Statistical Assessment of the Net Contribution of Climate Change to the Formation of Pollutant Concentrations in the Atmospheric Air Over the Territory of Ukraine - Савенець, Михайло; Крайник, Софія; Грама, Дар'я; Рудас, Марина; Скляр, Оксана (Київський національний університет імені Тараса Шевченка, 2025)
Background. Air pollution and climate change are among the key factors of negative anthropogenic impact on the environment. The variability of pollutants largely depends on emissions; however, the role of climate change in shaping pollutant concentrations remains insufficiently studied. This aspect is crucial for long-term planning to improve air quality and develop emission reduction strategies. This study presents an analysis of the net contribution of climate change to the formation of harmful pollutant concentrations using a statistical approach to time series decomposition. Methods. The research is based on monthly emission and concentration data of nitrogen dioxide (NO2), formaldehyde (CH2O), and tropospheric (ground-level) ozone (O3) from the Copernicus Atmospheric Monitoring Service (CAMS) reanalysis for the period from 2003 to 2021, as well as air temperature, wind speed, and precipitation data from the ERA5 reanalysis. The application of an additive statistical model allowed the decomposition of pollutant concentrations’ time series into seasonal (intra-annual) components, interannual trends, and interannual dependencies of NO2, CH2O, and O3 variability on fluctuations of climate parameters. Results. Seasonal variability in pollutants’ concentrations, which depends both on meteorological changes and differences in pollutant emissions, explains 61–74% of the total variability of NO2 and about 90% of CH2O and O3. The interannual trends of the studied pollutants, which are influenced by changes in anthropogenic load, ranged from 0.6% to 3.6% for NO2 and are generally below 1% for CH2O and O3, yet with statistically significant changes. The net contribution of climate change, assessed through the statistical relationship between interannual variations of pollutant anomalies and anomalies in climate parameters, showed that climate change accounts for less than 10% of the total pollutants’ variability. On average, this contribution is approximately 5% for NO2, 3% for O3, and only about 1% for CH2O. Conclusions. The obtained results indicate that the development of air pollution reduction strategies and air quality improvement should primarily focus on reducing direct anthropogenic emissions and their negative impact on public health and ecosystems. However, the role of climate change should also be considered as a significant factor in the formation of atmospheric pollution.

Вступ. Забруднення атмосферного повітря та зміна клімату є одними з основних чинників негативного антропогенного впливу на довкілля. Варіативність забруднюючих речовин більшою мірою залежить від викидів, проте залишається недостатньо вивченим роль зміни клімату у формуванні концентрацій, що важливо враховувати при довготерміновому плануванні покращення якості атмосферного повітря та стратегії зменшення викидів. У даній роботі представлено аналіз чистого внеску зміни клімату у формування концентрацій шкідливих домішок на основі застосування статистичного підходу до розкладання часових рядів. Методи. В основі досліджень лежать місячні дані викидів і концентрацій діоксиду азоту (NO2), фомальдегіду (CH2O) та тропосферного (приземного) озону (O3) із реаналізів Copernicus Atmospheric Monitoring Service (CAMS) за період з 2003 до 2021 рр., а також дані температури повітря, швидкості вітру і кількості опадів із реаналізу ERA5. Застосування адитивної моделі дозволило розкласти часові ряди концентрацій на сезонну (внутрішньорічну) складову, міжрічні тренди та міжрічну залежність варіативності концентрацій NO2, CH2O й O3 від мінливості кліматичних параметрів. Результати. Сезонна мінливість концентрацій, що залежить як від зміни метеорологічних умов так і відмінності у викидах забруднюючих речовин, пояснює від 61 до 74% загальної варіативності NO2, та близько 90% CH2O й O3. Міжрічні тенденції досліджуваних забруднюючих речовин, що залежать від зміни антропогенного навантаження, складають від 0,6% до 3,6% для NO2 та переважно менше 1% для CH2O й O3, проте зі статистично значущими змінами. Чистий внесок зміни клімату, оцінений через статистичну залежність міжрічних варіацій аномалій часових рядів забруднюючих речовин з аномаліями кліматичних параметрів, показав, що зміна клімату визначає менше 10% загальної варіативності концентрацій забруднюючих речовин. У середньому цей показник складає близько 5% для NO2, 3% для O3 та лише близько 1% для CH2O. Висновки. Отримані результати вказують на те, що розроблення стратегій зменшення викидів забруднюючих речовин та покращення якості атмосферного повітря, у першу чергу, має передбачати зменшення прямих антропогенних викидів і їх негативний вплив на здоров’я населення й екосистеми. Проте роль зміни клімату також має бути врахована як значущий чинник у формуванні атмосферного забруднення.
Статистичне оцінювання чистого внеску зміни клімату у формування концентрацій забруднюючих речовин в атмосферному повітрі над територією України
Keywords: діоксид азоту; формальдегід; тропосферний озон; забруднення атмосфери; адитивна модель; зміна клімату; nitrogen dioxide; formaldehyde; tropospheric ozone; air pollution; additive model; climate change